2002
DOI: 10.1038/sj.bjc.6600278
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of cigarette smoking and the risk of endometrial cancer

Abstract: Case -control studies have shown inverse associations between cigarette smoking and endometrial cancer risk. However, two small prospective cohort studies have not clearly supported an association. Moreover, quantitative measures of smoking have been examined infrequently. Our aim was to study the association between smoking and endometrial cancer risk in a large prospective cohort. We used proportional hazards models to estimate hazard ratios relating cigarette smoking to endometrial cancer risk among 70 591 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
1
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
6
22
1
1
Order By: Relevance
“…In our study, smoking women had a decreased risk of endometrial cancer, which is in agreement with other prospective cohort studies (Terry et al, 2002;Viswanathan et al, 2005;Al-Zoughool et al, 2007;Loerbroks et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…In our study, smoking women had a decreased risk of endometrial cancer, which is in agreement with other prospective cohort studies (Terry et al, 2002;Viswanathan et al, 2005;Al-Zoughool et al, 2007;Loerbroks et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, a decreased risk associated with passive smoking was observed for endometrial cancer, and a decreased risk associated with alcohol drinking was found for ovarian cancer. In Western countries, similar associations have been observed (Lyon et al 1983;Baron et al 1986;Kjaer et al 1996;Terry et al 2002;Viswanathan et al 2005). In Japan, although the evidence is sparse, Hirose et al have reported the increase in cervical cancer risk among active and passive smokers, and Kato et al found a decreased risk associated with alcohol drinking in ovarian cancer (Kato et al 1989;Hirose et al 1996).…”
Section: Discussionsupporting
confidence: 52%
“…Local immune suppression produced by tobacco smoking, which may enhance HPV persistence, may also affect the development of cervical cancer (Burger et al 1993). The association between smoking and endometrial cancer risk may be attributed to antiestrogenic effects of smoking (Terry et al 2002;Viswanathan et al 2005). Estrogen may promote the development of endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Besides bone fracture and IUD use, a third factor, which may link the etiology of ovarian and endometrial cancer, is smoking. A decreased risk for endometrial cancer is found in smokers, especially current smokers (29,30). The data are less clear for ovarian cancer with two recent studies suggesting that smoking may increase the risk only for mucinous histologic subtypes (31,32).…”
Section: Discussionmentioning
confidence: 62%